2011
DOI: 10.1007/s10681-011-0536-5
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes and self-incompatibility breakdown associated with autopolyploidization in Hylocereus species (Cactaceae)

Abstract: Chromosome duplication-autopolyploidization-may affect plant morphology and breeding systems, ultimately enabling the production of improved genotypes. In this study, the autotetraploid lines obtained from the self-incompatible diploid Hylocereus monacanthus and the autooctapolyploid lines obtained from the self-compatible tetraploid H. megalanthus were studied and compared with the donor accessions. The resulting H. monacanthus autotetraploids exhibit lower fruit weight, seed number, and pollen viability than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…The decrease in fruit weight and seed set in the autotetraploid and, more critically, in the autohexaploid, illustrated the disadvantages in plant fitness associated with the increase in ploidy levels in Hylocereus species. This conclusion is supported by the fact that the fruits obtained from induced autooctaploid (8 x ) H. megalanthus lines (obtained from germinating seeds) ceased developing at an early stage and aborted, resulting in almost zero fruit set [ 50 ]. The meaning of our findings is that enlarged cells (such as pollen or stomata) are a consequence of an increase in genome size (C-value) but that these changes are not systematically associated with the enlargement of other plant organs, as fruit weight or number of ovules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in fruit weight and seed set in the autotetraploid and, more critically, in the autohexaploid, illustrated the disadvantages in plant fitness associated with the increase in ploidy levels in Hylocereus species. This conclusion is supported by the fact that the fruits obtained from induced autooctaploid (8 x ) H. megalanthus lines (obtained from germinating seeds) ceased developing at an early stage and aborted, resulting in almost zero fruit set [ 50 ]. The meaning of our findings is that enlarged cells (such as pollen or stomata) are a consequence of an increase in genome size (C-value) but that these changes are not systematically associated with the enlargement of other plant organs, as fruit weight or number of ovules.…”
Section: Discussionmentioning
confidence: 99%
“…Genome size was assessed by comparing the nuclear DNA content of the diploid H. monacanthus and the allotriploid S-75 with the corresponding autopolyploid lines D-27 and D-2.3, as described in Cohen and Tel-Zur [ 50 ]. Each line was analyzed at least four times to verify reproducibility.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with the corresponding diploids, autopolyploids tend to have larger cells, which result in the enlargement of single organs, such as leaves, flowers and seeds [ 8 , 9 ]. Physiological traits such as plant height, growth rate, flowering time, and fertility also can be altered by polyploidization [ 10 - 12 ]. It has been shown that tetraploidization might significantly increase stress tolerance [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…A limited number of studies have investigated metabolic changes caused by autopolyploidization, and those studies focused on only specific metabolites [ 12 ]. The production of alkaloids was enhanced in artificial autotetraploids Hyoscyamus niger [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to get a hybrid clone that are self-compatible [SC] will be very beneficial to farmers so that farmers do not need to plant a variety of clones for the crossing [6] Cytoplasmic analysis gave the proof that hybrids are selfcompatible, and the hybrids are tetraploid. Thus polyploidy technique becomes important and gives prospective hope of solving their self-incompatibility in Hylocereusspp [7]. The quality and quantity of dragon fruit include sugar content, betalain pigment content and the overall condition of the fruit including weight and appearance thatareaffected by agronomic practices.…”
Section: Introductionmentioning
confidence: 99%